2011
DOI: 10.1186/1472-6963-11-164
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the assessment of chronic illness care (ACIC) instrument in Germany resulting in a new questionnaire: questionnaire of chronic illness care in primary care

Abstract: BackgroundThe Chronic Care Model (CCM) is an evidence based, population based approach to improve care for people with chronic conditions. The Assessment of Chronic Illness Care (ACIC) instrument is widely used to measure to what extent within a healthcare system the CCM is implemented. The aim of this study was to translate and culturally adapt the ACIC Instrument for the German healthcare system.MethodsFor translating the ACIC instrument, principles of Good Practice for the Translation and Cultural Adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
13
0
4
Order By: Relevance
“…O ACIC tem o potencial de ser afetado pelo papel de uma pessoa, do trabalho, do local e da compreensão dos elementos do MCC (SOLBERG ET AL., 2006). Itens como a organização do sistema de saúde, o autocuidado e o desenho de prestação de serviço foram os de mais difícil entendimento (STEINHAEUSER ET AL., 2011).…”
Section: Equipesunclassified
“…O ACIC tem o potencial de ser afetado pelo papel de uma pessoa, do trabalho, do local e da compreensão dos elementos do MCC (SOLBERG ET AL., 2006). Itens como a organização do sistema de saúde, o autocuidado e o desenho de prestação de serviço foram os de mais difícil entendimento (STEINHAEUSER ET AL., 2011).…”
Section: Equipesunclassified
“…Therefore different care providers are able to alter medication regimens without communication with the general practitioner (GP) [ 6 ]. To date there is no established patient tracking system in Germany and physicians' awareness of the impact of such interface problems seems to be low [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To measure progress within the Chronic Care Model, the Assessment of Chronic Illness Care [ 13 ] has been used in many settings, particularly in systems where multiple private insurers and providers play a greater role, and operate mainly in non-monopolistic delivery systems. Studies to measure the psychometric properties of Assessment of Chronic Illness Care have been performed in Germany [ 14 ], the Netherlands [ 15 ], Thailand [ 16 ] and the USA [ 17 ]. They have shown that Assessment of Chronic Illness Care has internal consistency and sensitivity.…”
Section: Introductionmentioning
confidence: 99%